Testing Theoretical Explanations for Investment Behaviour in the Dutch Beam Trawler Fishery in the North Sea - Frank Jensen; Christian Elleby; Katell G. Hamon; Jos op de Weegh (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2018)
In this study, we investigate whether neoclassical economic theory, capital market frictions or preference-based theory can explain investment behaviour in the Dutch beam trawler fishery in the North Sea. By presenting a number of estimations, we show that vessels conducting pulse fishing invest substantially more than similar vessels undertaking conventional fishing, even after controlling for differences in such variables as capital stock, prices, profits and quotas. One possible explanation for this result is that vessel owners may obtain a separate benefit from investing in pulse fishing.
Keywords: Q22; Q55; C23; 330; Fisheries; Investments; Conventional Fishing; Pulse Fishing